Relationship of the key elements of Knowledge management with strategic performance / filed research sample of private banks in Baghdad - الكبيسي, صلاح الدين عواد; اسكندر, شمس معزز (Journal of Economics and Administrative Sciences, 2017)
objective  the research to diagnosis and interpretation of the nature of the correlation between the  basic elements of knowledge management (tecgnology , structure , culture , process , human resource ) and the strategic performance of the Iraqi private banks, the research community and the level dimensions, and  tested this research in the private banking sector represented by (7), especially in Baghdad city, Iraqi banks, and applied on sample consisting of 100 distributors in several administrative levels Director (Director, Director of the department, branch manager), and use questionnaire Head to collect data and information tool, and some private banks annual reports, has sought research to test a number of hypotheses main and branch on the relationships of the link between research variables, and to answer all questions related to the problem of search has reached search to a group of results , most notably the presence of correlation of the elements of knowledge management dimensions with strategic performance for its removal .